#UNMASKEDSELFIESINSOLIDARITY: FROM SELF CARE TO COLLECTIVE CARE—AFFECTIVE ARTIVISM, NETWORKED BELONGING AND MOBILE MEDIA PARTICIPATORY ART. - Lanson, Klare Louise (AoIR Selected Papers of Internet Research, 2020)
Contemporary mobile media affords new insights into the social, critical, cultural and creative practice methods. With the continual rise of social practice in art which sees the “social” and “experience” as the medium, smartphones have become an increasingly important device for information dissemination, collective dialogue and poetic expression. This paper considers these insights through the lively and multivalent discussion of participatory art project entitled #UnmaskedSelfiesinSolidarity (2020) as case study. It is situated within the community of **** University international students, local students, staff and friends during the recent outbreak of the coronavirus in Wuhan, China, a global health event that has had significant socio-cultural, economic, and political impacts. It employs one of the most pervasive barometers of popular culture today, the selfie. Moving through related topics such as facial recognition and digital parenting, the #UnmaskedSelfies team recognise that now more than ever, we need transformative work to engage in collective care. In essence, this project has created an affective listening network to make the unheard heard, to voice personal concerns, and to show empathy for the broader community affected by this global health crisis. #UnmaskedSelfies openly supports international students caught in the crossfire of strict new travel restrictions imposed by the Government. We critically reflect on how art is a socially transformative process, through its messages of care alongside messages from Chinese students suffering anxiety and isolation, waiting for the travel bans to be lifted, a tempering of the stigma and racism accompanying the coronavirus event here in *COUNTRY*.